Interactions between Furosemide and Spironolactone in Normal Subjects - NAKAGAWA, FUJIO; UCHINO, KATSUYOSHI; ISOZAKI, SADAO; TANAKA, NAOMI; SAITOH, YUKIYA (Chemical & pharmaceutical bulletin, 1987)
Furosemide (FD) and spironolactone (SP) were co-administrated to human volunteers, and the pharmacokinetics and time course of diuresis were examined. The time courses of FD plasma concentration and diuresis after a single co-administration of FD plain tablet and SP were similar to those in the case of FD plain tablet. However, the plasma concentration of SP metabolites (determined as canrenone) during the 2-6 h period after a single co-administration of FD plain tablet and SP was about 0.05-0.15μg/ml higher than that after administration of SP. The steady-state distribution volume of SP metabolites after co-administration of FD plain tablet and SP was about 30% less than that after administration of SP, while the elimination rate constant of SP metabolites was about 1.5-fold greater. The diuresis during 24 h after a single administration of SP was 0.1-0.31. After multiple administration of SP, the plasma concentration of SP metabolites during the 2-6 h period after co-administration of FD plain tablet and SP was also about 0.1-0.3μg/ml higher than expected from the time course of SP metabolites simulated by using the data obtained after a single administration of SP. The elevation of SP metabolites concentration in plasma was prevented without any change of diuresis over 24 h by using FD retard capsule instead of FD plain tablet. We concluded that the phenomenon of elevation of SP metabolites concentration in plasma was caused by FD plain tablet, which induced strong diuresis and considerable loss of body fluids within a short time.